LIBERALISASI PENDIDIKAN TINGGI ISLAM DI INDONESIA (Studi Kasus Pengembangan IAIN) - Mustofa, Mustari (State Islamic Institute of Madura, 2009)
Developing islamic higher education as a scientific institution and for transforming islamic values is a must. The exertion of developing islamic higher education is taken by giving a wider mandate to IAIN to transform into UIN. This paper also emphasis to reform on every aspect of islamic higher education including the basis of philosophical thought laying, society services. lecture empowerment, and based higher education management.